Ejector type solid circulation system analysis for circulating fluidized beds - ÖZDOĞAN, ZEYNEP SİBEL (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Proper solid circulation is of crucial importance for the stable operation of circulating fluidized beds. There should be a pressure barrier between the riser and the downcomer to avoid reverse gas flow through the downcomer and to maintain a stable solid circulation. In conventional systems, loop seals, L, J, V, valves are mostly used as solid circulation valves. In this study, ejector (eductor) type solid circulation was investigated in an experimental CFB setup (94 mm in diameter, 7950 mm in height). The solid flux at the downcomer (34 mm in diameter) and the motive gas flowrate of the ejector were investigated under different cold flow conditions. There are two different operation modes of the ejector type solid circulation depending on the solid flux through the downcomer. For low solid fluxes, there is no solid accumulation at the downcomer. As the solid flux increases, a solid column formation is observed above the ejector system. The desired pressure difference obtained with the ejector is higher for the latter mode of operation and requires less motive gas flow compared to the former for proper operation. The experimental results show that the ejector is capable to provide the required pressure barrier for the CFB loop in both cases. In addition to the experimental study, ejector system was analyzed with CFD model in order to investigate the effect of basic geometric and operational parameters on the pressure difference generated by the ejector. Furthermore a novel semi-empirical method was proposed as a tool for predicting the ejector performance comparable with CFD results. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Circulating fluidized bed; Solid circulation; Cold model; Eductor, ejector; CFD; STEAM EJECTOR; CFD ANALYSIS; NUMERICAL ASSESSMENT; OPERATION; VALIDATION; SIMULATION; DYNAMICS; NOZZLE